SHAPING THE IMAGE OF THE SCHOOL AS A COMPETENCE SKILL - Karolina Studnicka-Mariańczyk (Pavlo Tychyna Uman State Pedagogical University, 2018)
The article deals with the shaping the image of the school as one of the important issues of the secondary institution existence. The author states that a positive image of the organization is associated with high reputation and therefore belongs to the most valuable resources. Favourable or unfavourable image of the organization in social perception, which may arise not only due to direct contact with the organization and its employees, has been characterized. It has been proved by the author that the image of the organization can also arise through informal contacts. The concept of such terms as «adequate communication», «image» has been explained. A positive, beneficial image of the organization, both external and internal, is defined to be one of the extremely valuable resources of the organization. It can be one of the key success factors, motivating to achieve goals and conditioning the achieved results, and indirectly the formation of a positive image usually indicates the correct functioning of the institution and the effectiveness of the strategy. Moreover, it has been said that it may also be a condition for the effectiveness of the organization's activities and occur as a factor enabling its harmonious development, a factor stimulating the attitudes of employees and the external environment, harmonizing the organization and the environment, as well as an important element of employee's identity and organizational culture. The image of the institution also plays an important role in relation to the school's functioning. Creating the right image is one of the important skills of the principal. By his attitude, personal culture and attention to the proper functioning of the educational institution, he contributes to the creation of an advantageous opinion about the institution. This impact can be effectively reinforced through the use of conscious treatments to create a designed image. It has been stated that the opportunity for this is formed by contacts with parents, participation in school celebrations and in the city, meetings with journalists, all public appearances. The author makes the conclusion that the principles of cooperation and the atmosphere that defines day-to-day contacts, which make up this culture, not only contribute to the creation of a favourable image of the institution, but also capture the image, as well as the results obtained in educational work. Skilful information about the achievements of the school is in this context a factor which strongly affects the awareness of people in the internal environment of the school and beyond. Knowledge about management processes helps to set strategies and lead them to the future. Thus, ability to create a positive image of a school turns out to be an impor-tant management factor - an element that is part of the principal's management and social competence.